A colorimetric technique to characterize mass transfer during liquid-liquid slug flow in circular capillaries - Yanyan Liu (MethodsX, 2021)
Continuous slug flow in microreactors are featured by alternative presence of regulate segments of immiscible phases in microchannel or capillaries with lateral dimensions below 1 mm. Due to the high interfacial area and short diffusive distance therein, such microreactors have been widely applied in chemical engineering processes that are sensitive to mass transfer. Therefore, mass transfer rates in microreactors have long been broadly investigated via either typical offline or online methods. Compared to these conventional methods, the colorimetric technique based on the oxidation of resazurin with oxygen enables direct determination of physical mass transfer rates. However, this technique was currently applied only to the gas-liquid system in microreactors, and mostly in rectangular channels due to the simplicity in image processing. Based on this, the current paper showed a demo where the colorimetric technique using resazurin was adapted to a liquid-liquid system for the mass transfer study of flowing droplets within a slug flow capillary. Experimental tips and tricks were summarized, and a sliced color-concentration calibration strategy was proposed to balance analyzing efficiency and accuracy.